2012
DOI: 10.1016/j.mayocp.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Loci Implicated in Erythroid Differentiation and Cell Cycle Regulation Are Associated With Red Blood Cell Traits

Abstract: Objective: To identify common genetic variants influencing red blood cell (RBC) traits. Patients and Methods: We performed a genomewide association study from June 2008 through July 2011 of hemoglobin, hematocrit, RBC count, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration in 12,486 patients of European ancestry from the electronic MEdical Records and Genomics (eMERGE) network. We developed an electronic medical record-based algorithm that included individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…A GWAS study reported that an SNP (rs11107) causing a Met115Ile change in Fbxo7 is associated with a 0.35-fl decrease in MCV [11]. Given our findings, we tested whether p27 binding was sensitive to this residue in Fbxo7.…”
Section: Resultsmentioning
confidence: 92%
“…A GWAS study reported that an SNP (rs11107) causing a Met115Ile change in Fbxo7 is associated with a 0.35-fl decrease in MCV [11]. Given our findings, we tested whether p27 binding was sensitive to this residue in Fbxo7.…”
Section: Resultsmentioning
confidence: 92%
“…To do this, we employed a previously developed algorithm based on billing codes and natural language processing of unstructured clinical notes to exclude RBC traits values affected by comorbidities, medications, or blood loss (Ding et al 2012; Kullo et al 2010, 2011). The phenotyping algorithm is available online (www.gwas.org), and the values of RBC traits before and after implementing the algorithm are provided in Supporting Information, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have revealed multiple loci that influence interindividual variation in RBC traits in individuals of European and Asian ancestry (Ding et al 2012; Ganesh et al 2009; Kamatani et al 2010; Kullo et al 2010; Soranzo et al 2009). Whether these and additional novel loci influence RBC traits in individuals of recent African ancestry is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that adding T3 to the culture medium of erythroid progenitors promoted erythroid differentiation (Angelin-Duclos et al, 2005). A genome-wide association study indicated that an intronic single nucleotide polymorphism (rs9310736) in THRB was significantly associated with mean corpuscular volume (Ding et al, 2012). These data implied that THRB plays a role in erythroid differentiation.…”
Section: Discussionmentioning
confidence: 87%